Calls for thunderstorm safety lessons - New Straits Times, (2012)
KUALA LUMPUR: Thunderstorm safety education should be made compulsory in schools as an early measure to prevent mishaps from occuring,said a lightning protection expert from Universiti Putra Malaysia. Director of Centre of Excellence on lightning Protection Associate Prof Dr Mohd Zainal Abidin Ab Kadir said society was not that concerned with safety as outdoor activities were still conducted during thunderstorms. "When thunderstorms occur,all indoor and outdoor activities must stop to avoid damage to property and personal injury. The public only take prenetive measures after deaths,injuries and damage to property occur." Bernama